Can green sustain growth? : from the religion to the reality of sustainable prosperity - John Zysman (Springer, 2015)
Green growth promises to transform climate change mitigation from a problem to an economic sure thing. By making investment in energy efficiency and low-emissions energy the foundation of a new industrial revolution, green growth promises to relieve the intractable conflict between high-carbon losers and low-carbon winners. This book addresses the challenges and opportunities for green growth.